Pelatihan Videografi dalam Pengemasan Video Jurnalistik menggunakan Adobe Premiere di SMK Negeri 2 Garut - Nurfaza, Najmi; Salamah, Ummu (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The objective of this program is to enhance students' technical skills in videography and video editing using Adobe Premiere. Through this training, students are expected to be better prepared to pursue careers in the media and communication fields. Methodology: This program is conducted through training sessions and workshops specifically designed for 11th-grade students majoring in Television Broadcast Production. The training involves the use of tools such as the A6000 camera, tripod, stabilizer, laptop, and Adobe Premiere Pro CC 2022 software. The methodology includes live demonstrations, hands-on practice, and Q&A sessions to ensure a deep understanding. Results: The program yielded very positive results. More than 80% of students reported gaining new knowledge about the features of Adobe Premiere. Additionally, over 90% of students expressed a strong interest in attending more similar training sessions in the future, demonstrating a high level of enthusiasm for videography and video editing. Conclusions: This program successfully transferred knowledge from the academic environment to the community, strengthened the community, and supported the development of specific industries or sectors. The goals of the program were achieved effectively, providing a significant positive impact for both the participants and the community. The improvement in students' knowledge and skills made them more proficient in videography and video editing. Limitations: The limitations of this program include resource constraints, such as limited availability of equipment and restricted time for conducting training sessions and workshops. Additionally, the variability in the initial skill levels of students can also affect the effectiveness of the training. Contribution: This program made a significant contribution to the development of students' knowledge and skills in videography and video editing. Additionally, the program successfully fostered students' interest and enthusiasm for multimedia technology, which could encourage them to pursue careers in the field in the future.